PROMIS Mali Baseline Data 2015, Child Level - International Food Policy Research Institute; AfricSanté (International Food Policy Research Institute, 2019)
The dataset contains baseline data of the impact evaluation in Mali of the “Innovative Approaches for the Prevention of Childhood Malnutrition” (PROMIS) project, which integrated a preventive intervention package into Community Management for Acute Malnutrition (CMAM) programming in Mali and Mali. Using cluster-randomized designs, we evaluated the impact of integrating preventive services into screening for child acute malnutrition on acute malnutrition screening and treatment coverage and acute malnutrition prevalence and incidence. The PROMIS program sought to address the low screening coverage in Mali by integrating small-quantity lipid-based nutrient supplement (SQ-LNS) into community-based screening for Acute Malnutrition. The intervention was implemented by Helen Keller International through the national health system. Data were collected by the International Food Policy Research Institute (IFPRI) in collaboration with AfricSanté.